2021
DOI: 10.2471/blt.19.249656
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an infant male circumcision programme, Pakistan

Abstract: Objective To retrospectively review outcomes of a health provider-led infant circumcision programme in Pakistan. Methods Based on World Health Organization guidelines, we trained surgical technicians and midwives to perform circumcisions using the Plastibell device at two Indus Health Network facilities. Programme tools include a training manual for health providers, information brochures for families, an enrolment form and standardized forms for documenting details of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Circumcision is common in pediatric urology [ 1 , 2 ], with a prevalence of about 7% [ 3 ]. Currently, dorsal penile nerve block anesthesia is the main anesthetic method, and circumcision under basic anesthesia is the mainstay of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Circumcision is common in pediatric urology [ 1 , 2 ], with a prevalence of about 7% [ 3 ]. Currently, dorsal penile nerve block anesthesia is the main anesthetic method, and circumcision under basic anesthesia is the mainstay of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended circumcision to be performed on infants aged below 3 months. 19 In each community, the best timing of this procedure is defined by tradition and faith. Parental decision on neonatal or older boys’ circumcision is usually based on the parent's choice and accurate knowledge received from health workers.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Pakistan showed that older children had a higher risk of complications than infants. They recommended circumcision to be performed on infants aged below 3 months 19 . In each community, the best timing of this procedure is defined by tradition and faith.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circumcision is one of the most common practices around the world, which is routinely performed to adhere to the teaching of Prophet Abraham. There is a general belief that performing such a practice does not violate human integrity nor cause any kind of moral inadequacy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%